La multimedia como herramienta para el aprendizaje autónomo del vocabulario del inglés por parte de los niños - Moreno Mosquera, Francisco (Colombian Applied Linguistics Journal, 2011)
This paper describes a pedagogical intervention carried out at the University of Chocó aimed at determining the degree of effectiveness of multimedia technology as a tool for independent learning of English vocabulary by children. The research problem was stated in terms of the questions: ¿how effective is foreign language learning through technology?, ¿how much can children in Chocó learn English vocabulary by themselves through multimedia? The indings conirm several hypotheses about the learning of vocabulary and pronunciation, and leads the researchers to conclude that multimedia is effective as a teaching tool for autonomous learning of foreign languages.